The CT-Based Patient Specific Hip Joint 3D-Modeling; Potential to Correct the Alignment - Saveh, Amirhossein; Zali, Ali Reza; Haghighatkhah, Hamidreza; Sanei Taheri, Morteza; Kazemi, Seyed Morteza; Chizari, Mahmoud; Gammada, Kazuyoshi (International Clinical Neuroscience Journal, 2014)
Background: The salvage proximal femoral osteotomy is performed in mild or moderate osteoarthritis when the articulating surfaces are normal and relieves the subject’s pain. Because the importance of angular mal-alignment of the femur bone at the hip junction accurate pre-op planning based on patient specific anatomy is required to prevent any lower limb misalignment and joint problem pre-operative. Methods: In this study a CT-Based modeling technique was used to generate a 3D model of the patient’s hip and proximal femur. The registration stage using angio-fluoroscopy was performed to calculate the proximal femur kinematic and input it into a finite element model to achieve the stress distribution pattern of femuroacetabular joint. Results:From finite element model the stress distribution on the articulating surface at the contact zone was analyzed. The result was showing the maximum stress of 1.1 MPa at the contact surface where femur contact the acetabulum. The maximum stress is found in line with mechanical loading of the lower limb. Conclusion: Use of a non-invasive 3D modeling method will remediate the surgical approach in pre-op stage. The in-vivo modeling and assessment of the patient femoroacetabular contact has performed. It has been shown that the accuracy of the proposed model is comparable with the existing surgical pre-op planning.